1991
DOI: 10.1093/carcin/12.2.317
|View full text |Cite
|
Sign up to set email alerts
|

The potent anti-tumor-promoting agent isoliquiritigenin

Abstract: A topical application of a chalcone derivative, 4,2',4'-trihydroxychalcone (isoliquiritigenin) inhibited epidermal ornithine decarboxylase (ODC) induction and ear edema formation, i.e. inflammation, caused by a topical application of 12-O-tetradecanoylphorbol-13-acetate (TPA) in CD-1 mice. In addition, isoliquiritigenin potently inhibited 7,12-dimethylbenz[alpha]anthracene (DMBA)-initiated and TPA-promoted skin papilloma formation. This inhibitory effect of isoliquiritigenin was not due to any damage inflicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 0 publications
0
90
0
Order By: Relevance
“…Isoliquiritigenin (ISL), a flavonoid with chalcone structure (2,4,4 0 -trihydroxychalcone), which exists in licorice and in vegetables including shallots and bean sprouts (Cao et al, 2004;Ii et al, 2004;Kape et al, 1992), has been shown to exhibit a variety of biological activities, including antioxidant (Chin et al, 2007;Haraguchi et al, 1998), antiinflammatory (Kim et al, 2008), estrogenic properties (Tamir et al, 2001), analgesic (Chan et al, 1998;Morteza et al, 2004), cytoprotective effects (Kim et al, 2004), antiplatelet aggregation (Chisato et al, 2008;Tawata et al, 1992), antipeptic ulcer actions (Kim et al, 2006), chemopreventive agent (Hsu et al, 2005a), antiangiogenic effect (Kobayashi et al, 1995), radical-scavenging activity (Yamamoto et al, 1991) and antitumor activities (Baba et al, 2002;Iwashita et al, 2000;Jung et al, 2006b;Kanazawa et al, 2003;Ma et al, 2001;Maggiolini et al, 2002;Takahashi et al, 2004;Yamazaki et al, 2002). In particular, ISL can suppress proliferation of many types of cancer cells and induce their apoptosis, including HL-60 human promyelocytic cell line (Chowdhury et al, 2005), colon cancer cells (Takahashi et al, 2004), gastric cancer cells (Ma et al, 2001), breast cancer cells (Maggiolini et al, 2002), human prostate cancer (Jung et al, 2006a,b) and human hepatoma cells (Hsu et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Isoliquiritigenin (ISL), a flavonoid with chalcone structure (2,4,4 0 -trihydroxychalcone), which exists in licorice and in vegetables including shallots and bean sprouts (Cao et al, 2004;Ii et al, 2004;Kape et al, 1992), has been shown to exhibit a variety of biological activities, including antioxidant (Chin et al, 2007;Haraguchi et al, 1998), antiinflammatory (Kim et al, 2008), estrogenic properties (Tamir et al, 2001), analgesic (Chan et al, 1998;Morteza et al, 2004), cytoprotective effects (Kim et al, 2004), antiplatelet aggregation (Chisato et al, 2008;Tawata et al, 1992), antipeptic ulcer actions (Kim et al, 2006), chemopreventive agent (Hsu et al, 2005a), antiangiogenic effect (Kobayashi et al, 1995), radical-scavenging activity (Yamamoto et al, 1991) and antitumor activities (Baba et al, 2002;Iwashita et al, 2000;Jung et al, 2006b;Kanazawa et al, 2003;Ma et al, 2001;Maggiolini et al, 2002;Takahashi et al, 2004;Yamazaki et al, 2002). In particular, ISL can suppress proliferation of many types of cancer cells and induce their apoptosis, including HL-60 human promyelocytic cell line (Chowdhury et al, 2005), colon cancer cells (Takahashi et al, 2004), gastric cancer cells (Ma et al, 2001), breast cancer cells (Maggiolini et al, 2002), human prostate cancer (Jung et al, 2006a,b) and human hepatoma cells (Hsu et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…inhibitory effect on aldose reductase, 6) anti-tumor promoting effect on two-stage skin tumor formation, 5) suppressive effect against 5-lipoxygenase, 5) antioxidative and superoxide scavenging activities, 8) etc. Topical application of ILG suppress the 12-O-tetra-decanoylphorbol-13-acetate (TPA) or bromomethylbenz [a]anthracen-induced skin tumor formation, 5) and acute inflammation in mouse ear, 5) however, oral administration of this compound showed weak activity on two-stage lung and skin carcinogenesis in our previous studies (unpublished data). These results indicated that the suppressive effect of ILG might be due to direct action against the organs.…”
Section: Resultsmentioning
confidence: 99%
“…4) Other biological activities for this compound have also been reported. For example, antitumor promoting activity on two-stage mouse skin carcinogenesis, 5) inhibitory effect on aldose reductase activity, 6) antiplatelet aggregation effect, 7) antioxidative and superoxide scavenging activities, 8) etc. However, all these experiments were in vitro or topical application in vivo, and there is no reported data of the effect by oral administration in vivo.…”
mentioning
confidence: 99%
“…This compound inhibited TPA-independent tumor promotion in mice treated with DMBA and suppressed TPA-stimulated production of PGE2 in intact epidermal cells. However, it seems that isoliquiritigenin (2) exerts its antitumor-promoting effect through the lipoxygenase (LOX) inhibition in nonepidermal cells because it failed to inhibit 12-LOX and COX in an epidermal subcellular fraction [177]. Ye et al [182] recently demonstrated that isoliquiritigenin (2) inhibits the CYP19 enzyme (aromatase), which catalyzes rate-limiting step of the conversion of androgens, such as testosterone and androstenedione to estrogens.…”
Section: Effects Of Chalcones On Tumor Promotionmentioning
confidence: 99%